(untitled) (Contemporary Research: An Interdisciplinary Academic Journal, 2020)
This article aims to explain the effectiveness of using Information and Communication Technology (ICT) in teaching and learning school mathematics. The paper is based on the results of one month experiment of Geo Gebra software in teaching and learning the concepts and problems included in the chapter commensuration of secondary level mathematics. The effectiveness of using ICT tools were explored by measuring achievement level with the help of achievement test and overall perceptions of using ICT tools through questionnaire. The data were analyzed and interpreted by using table, frequency, percentage, mean, SD and t-test. The findings revealed that there was high mean score in achievement in mathematics of experimental group (teaching with ICT) than that of control group (without using ICT), and the difference was significant at 0.05 level. Likewise, the students of experimental group had positive perception to support the use of ICT tools in teaching and learning mathematics. Thus, the use of ICT, particularly Geo Gebra is an effective tool to increase achievement; to promote curiosity, creativity; to make clear sense of concepts; and to encourage overall learning of students in mathematics. Finally, the study suggests that school mathematics teachers need to use ICT for effective teaching and learning.